2017
DOI: 10.2903/j.efsa.2017.5057
|View full text |Cite
|
Sign up to set email alerts
|

Safety of betaine as a novel food pursuant to Regulation (EC) No 258/97

Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on betaine as a novel food (NF) pursuant to Regulation (EC) No 258/97. The information provided on the composition, the specifications, the batch-to-batch variability, stability and production process of the NF is sufficient and does not raise concerns about the safety of the NF. The NF is proposed to be used in foods intended to meet additional requirements for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…In 2017, in its scientific opinion on betaine, the Panel concluded that an amount up to 6 mg/kg bw per day of betaine in addition to the intake from the background diet is considered safe (EFSA NDA Panel, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2017, in its scientific opinion on betaine, the Panel concluded that an amount up to 6 mg/kg bw per day of betaine in addition to the intake from the background diet is considered safe (EFSA NDA Panel, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Panel notes that the mean and high-level (95th percentile) estimated intakes of betaine for the general population do not exceed the safe level of intake as previously established by the NDA Panel, i.e. 6 mg/kg bw per day in addition to the intake from the background diet (EFSA NDA Panel, 2017).…”
Section: 3mentioning
confidence: 92%
See 2 more Smart Citations
“…Regarding betaine, addition to beverages, cereal products, confectionary, or dairy products in the EU was firstly intended fifteen years ago, but the available data were not sufficient to rule out the safety concerns (Table 2) [19]. Nonetheless, recent scientific opinions of the European Food Safety Authority (EFSA) expressed no safety concerns to the addition of betaine in novel foods for intense muscular effort, foods for sportsmen, weight control, and special medical purposes, under determined conditions (Table 2) [2,20]. This has led to its inclusion in the positive list of authorized novel foods [21].…”
Section: Maintenance Of Normal Liver Functionmentioning
confidence: 99%